Democratic government in India - "Srinivasan, N." (Calcutta, 1954)
A textbook on the democratic Government functioning in India is undoubtedly a necessity. I do not know if pupils in Indian schools have been told about this great experiment of ours and how this experiment would influence the moral and material progress of the future generations.
Keywords: Democracy